UTILIZATION OF CAPITAL FOR ECONOMIC AND SOCIAL DEVELOPMENT - RFS, Harapan Tua; Meilani, Nur Laila; Sadad, Abdul; Meiwanda, Geovani; Amri, Khairul; Putra, Indra Mardeni; Zulkarnaini, Zulkarnaini (Universitas Padjadjaran, 2025)
This study is based on a policy innovation introduced by the Siak Regency Government related to village economic growth, particularly in Sungai Apit Sub-district. Through Law No. 6 of 2014, the government provides opportunities for each village to establish a business entity that can meet community needs—especially basic needs—while utilizing untapped local natural resources. These entities are expected to be managed as strategic assets that drive the local economy. Inclusive economic growth refers to efforts to ensure that the benefits of development are distributed across all segments of society, including rural communities. With the presence of small and medium enterprises (SMEs), creative industries, and agribusiness, local residents are no longer required to migrate to urban areas in search of employment. Empowerment programs—such as education, skills training, and community capacity building—can enhance their ability to actively participate in economic and social development. This study applies the Community Capitals Framework (CCF) developed by Emery and Flora (2006), which consists of seven dimensions. A qualitative method is employed to explore and identify patterns in how different forms of capital operate within the Sungai Apit Sub-district community in Siak Regency. The findings indicate that the condition of each type of capital shows an increasing trend in both quantity and quality. By effectively utilizing these various forms of capital—through educational programs, cultural initiatives, financial resources, and environmental conservation—Sungai Apit Sub-district is projected to improve its long-term well-being, resilience, and prosperity. Through collaboration, participation, and capacity building, communities can create a virtuous cycle in which different forms of capital reinforce one another, leading to sustainable and positive development outcomes.